2021
DOI: 10.3348/kjr.2020.0331
|View full text |Cite
|
Sign up to set email alerts
|

CT-Guided Microcoil Localization of Small Peripheral Pulmonary Nodules to Direct Video-Assisted Thoracoscopic Resection without the Aid of Intraoperative Fluoroscopy

Abstract: Objective To evaluate the feasibility, safety, and effectiveness of CT-guided microcoil localization of solitary pulmonary nodules (SPNs) for guiding video-assisted thoracoscopic surgery (VATS). Materials and Methods Between June 2016 and October 2019, 454 consecutive patients with 501 SPNs who received CT-guided microcoil localization before VATS in our institution were enrolled. The diameter of the nodules was 0.93 ± 0.49 cm, and the shortest distance from the nodules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…The reported rates of intrapulmonary hemorrhage following microcoil localization range 4.1 to 27.3%. 12,18 In the present study, the incidence of pulmonary hemorrhage in both groups was in line with the current literature. An increase in the distance from the microcoil to the pleura inevitably increases the chance of penetrating the pulmonary vessels, and vascular tears cause more complications of intrapulmonary hemorrhage.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The reported rates of intrapulmonary hemorrhage following microcoil localization range 4.1 to 27.3%. 12,18 In the present study, the incidence of pulmonary hemorrhage in both groups was in line with the current literature. An increase in the distance from the microcoil to the pleura inevitably increases the chance of penetrating the pulmonary vessels, and vascular tears cause more complications of intrapulmonary hemorrhage.…”
Section: Discussionsupporting
confidence: 92%
“…The localization technique described by Huang et al 12 was used in the conventional localization group. First, the patient was placed on the CT scan bed in a suitable position (prone, supine, or lateral).…”
Section: Localization Proceduresmentioning
confidence: 99%
“…8 Recently, several studies have reported the use of CT-guided hookwire or microcoil for preoperative localization of SMPNs, which showed a good success rate, but had various complication rate, including pneumothorax and pulmonary hemorrhage. [10][11][12][13][14][15][16][17] Therefore, the aim of this study was to retrospectively analyze the incidence and predictors of complications related to hookwire localization both in patients with single and multiple nodules, as well as to evaluate the usefulness of a single-stage surgical method of single hookwire localization combined with VATS in SMPNs.…”
Section: Introductionmentioning
confidence: 99%
“…Common methods include preoperative CT-guided percutaneous placement of hook wires and microcoils. Nonetheless, these procedures may cause complications such as pneumothorax and active bleeding and increase the risk of displacement [12][13][14][15][16]. Other methods involve CT-guided percutaneous placement of radioactive particles or dyes such as methylene blue, but these also lead to complications and additional challenges [17].…”
mentioning
confidence: 99%